2017
DOI: 10.12957/psi.saber.soc.2017.30670
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de drogadição e práticas sociais entre moradores de rua

Abstract: RESUMO:Este artigo apresenta dados que indicam a existência de três grupos sociais entre os moradores de rua: os alcoolistas, os adictos de crack e os polidrogaditos. Para isto, utiliza-se do arcabouço teórico e metodológico da abordagem estruturalista das representações sociais para demonstrar que cada grupo é reconhecido entre os moradores de rua como tendo um perfil de práticas. A amostra é composta por uma população de internos de uma instituição não governamental, que se dedica exclusivamente ao cuidado d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
3
0
9
Order By: Relevance
“…For participants, abstaining from alcohol contributes to positive attitudes in self-care, such as eating, bathing, sleeping, working, preventing oneself. Studies carried out with HP on the use of alcohol and other drugs indicate that this behavior is an alternative for street survival (7,(35)(36)(37) . The words "good relations" were the third most evoked, revealing the need to avoid confusion, not to fight, know what to see and what to speak on the streets, as well as to define who to hang around with, thus protecting themselves from situations of violence and/or trouble.…”
Section: Discussionmentioning
confidence: 99%
“…For participants, abstaining from alcohol contributes to positive attitudes in self-care, such as eating, bathing, sleeping, working, preventing oneself. Studies carried out with HP on the use of alcohol and other drugs indicate that this behavior is an alternative for street survival (7,(35)(36)(37) . The words "good relations" were the third most evoked, revealing the need to avoid confusion, not to fight, know what to see and what to speak on the streets, as well as to define who to hang around with, thus protecting themselves from situations of violence and/or trouble.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar do grande número de pessoas nessa condição no mundo todo, tradicionalmente essa população é invisibilizada pelas discussões acadêmicas. No entanto, vem crescendo nos últimos anos a produção científica sobre tal realidade (Guerreiro & Palma, 2010;Spadoni et al, 2017;Silva et al, 2018;Carrascal & Londoño, 2009;Rubio-Martín, 2017;Renedo, 2013). Historicamente a população em situação de rua foi e continua sendo invisível para a sociedade e para o Estado.…”
Section: Revisão De Literaturaunclassified
“…A síntese foi realizada a partir da correspondência com o objetivo inicial do estudo, a fim de contribuir na produção de estudos relacionados à temática, além de evidenciar lacunas existentes na literatura científica. (Carrascal & Londoño, 2009;Guerrero & Palma, 2010;Spadoni et al, 2017;Silva et al, 2018). Em relação ao tipo de pesquisa, duas referiam-se à abordagem mista, duas eram qualitativas, uma era quantitativa e era uma documental.…”
Section: Métodounclassified
“…However, the street condition can also lead to drug addiction. 3 One study pointed to alcohol and crack as the most used drugs by homeless people (26.7%, and 23.37, respectively), as well as drugs of higher addiction, especially when there is an association between them 3 . All interviewees in the study reported making use of drugs; only 25.3% reported not being dependent on the drugs used.…”
Section: Introductionmentioning
confidence: 99%
“…All interviewees in the study reported making use of drugs; only 25.3% reported not being dependent on the drugs used. 3 In this sense, the inclusion of the Street Clinic teams (SCt) by the National Primary Care Policy of 2011, and as a care device of the Psychosocial Care Network (PSCN), through ordinance 3088/2011, was essential for the population especially for those with problems related to the use of Alcohol and Other Drugs (AOD).…”
Section: Introductionmentioning
confidence: 99%